Legislative Powers Inperspective Fiqih Siyasah - Hasannudin Hidayat (International Journal of Education, Information Technology, and Others, 2020)
Legislative power is one of the important elements in a modern state order, usually in a country it is known as the branch of power in charge of organizing the life process of the state, the executive, legislative and judicial branches of power that simultaneously work to realize the goals and ideals of the state, namely provide happiness and welfare for the greatest prosperity of its people. In this study, an analysis with regard to legislative power will be presented which the researcher emphasizes in a comparative study between the conception of legislative power in the perspective of Islamic constitutional law (fiqih siyasah) and the conception of legislative power in the context of positive constitutional law in Indonesia. This study uses a normative and descriptive analytical juridical approach as well as a comparative study to analyze topics related to legislative power in the perspective of siyasah fiqh and its comparison with legislative power in the perspective of positive constitutional law prevailing in Indonesia